Can family ownership influence firms' capital structure decisions? - Medeiros, Catarina Lobo Moutinho Melo (2015)
The purpose of the present study is to endeavor the explanatory capacity of family ownership in determining the capital structure of the firms. Having this purpose in mind, we collect and analyze information for the period 2005-2013, regarding a sample of 194 family and non-family businesses, whose headquarters' location is in either European or North American countries. We obtain empirical evidence to conclude that i) non-family firms present higher leverage ratios compared to their family peers; and ii) non-family firms rely more on long-term debt than their family peers. Our study adds value to previous research since it compares companies from two different continents, (North) America and Europe, it analyzes how different firm characteristics may influence both leverage ratio and long-term debt to total debt and finally because it studies the impact of the financial crisis on the firms' financial results.